Factors influencing Chinese female college students' willingness to receive human papillomavirus vaccine: A cross-sectional study based on information-motivation-behavioral skills model. Issue 7 (30th December 2022) - Wang, Hong; Wang, Xiaoyang; Chen, Peipei; Xu, Huifang; Liu, Yin; Kang, Ruihua; Zheng, Liyang; Sun, Xingyuan; Sun, Xibin; Qiao, Youlin; Zhang, Shaokai
ABSTRACT: China bears heavy disease burden of cervical cancer, but the willingness to receive human papillomavirus (HPV) vaccine is low. This study aimed to assess the factors affecting the willingness of Chinese female college students to receive HPV vaccine based on the information-motivation-behavior skills (IMB) model. A cross‑sectional study was carried out in Henan University of Engineering in February 2020. Demographic characteristics and IMB model variables were collected using an anonymous questionnaire. A structural equation model was constructed to assess influencing factors of HPV vaccination willingness in the IMB model variables using AMOS 24.0. A total of 449 participants completed the survey. Among them, 23.4% were willing to get the HPV vaccine in the next 6 months. The average scores of knowledge, motivation, and behavioral skills were 1.72 ± 1.07, 11.69 ± 1.71, and 10.14 ± 1.86, respectively. The final revised model indicated a good fit to the data (χ 2 /df = 1.684, goodness of fit index = 0.984, adjusted goodness of fit index = 0.959, root mean square error of approximation = 0.044). The results of the model showed that the behavioral skills (β = 0.318, P < .001) were positively related to the willingness of HPV vaccination uptake among female students. Moreover, motivation (β = 0.475, P < .001) positively affected students' behavioral skills toward HPV vaccination, which further influenced their willingness of HPV vaccination uptake. HPV-preventive interventions for female students should focus on enhancing motivation and strengthening behavioral skills to increase the willingness to receive HPV vaccine and reduce HPV infection.